Does leadership matter for healthcare service quality? Evidence from NHS England. Issue 2 (4th March 2023) - Elkomy, Shimaa; Murad, Zahra; Veleanu, Veronica
Abstract: In this article, we provide first-hand evidence that leadership quality matters for the quality of healthcare provision, based on NHS England hospital trust data between 2010 and 2014. This is the first paper to study this relationship using individual leadership styles, namely, task-, relations-, change- and integrity-oriented as independent variables and four different metrics of quality of healthcare as dependent variables, including staff and patient satisfaction survey measures and clinical performance indicators. We find that task-oriented leadership has the strongest effect on staff-rated hospital quality while change-oriented leadership affects most patient satisfaction and the clinical measure. We also find some evidence that organizational autonomy and competition across hospitals moderates the effect of leadership quality on healthcare quality. Overall, our results have important policy implications for continued support for the development and funding of integrated leadership programs in healthcare.